Implementasi Sikap Anti-Bullying dan Anti-Rasisme di Sekolah Dasar Berupa Penggunaan Audio Visual - Amrullah Al Fahmi; Amellia Rizki Febrianti; Rafli Akbar Maulana; Eka Dian Safitri; Muhammad Akbar Rafsanjani; Lucky Ardina Risma; Dimas Raihan Akbar; Muhammad Burhanuddin Irsyadi; Dimas Bastara Zahrosa; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Education plays a central role in shaping students' character, morals, and knowledge to develop critical, creative, and ethical thinking abilities. However, the prevalence of bullying and racism in schools indicates a moral crisis and insufficient implementation of character values among students. The community service activity was conducted at SDN Dawuhan with the aim of instilling anti-bullying and anti-racism character from an early age to create a safe, harmonious, and conducive school environment. The implementation method employed a descriptive approach with audio-visual media and the administration of pre-tests and post-tests to measure students' understanding before and after the activity. Pre-test and post-test results revealed that prior to the community service, students lacked comprehensive understanding of bullying and racism. Comparison of pre-test and post-test results showed approximately 75% improvement in understanding after material presentation. The activity was conducted through three sessions from September 12, 2025, to September 26, 2025, with third-grade elementary school students as research subjects. Results demonstrated increased understanding and behavioral changes regarding the importance of respecting differences, as well as decreased bullying cases in the school environment. Students became more open, communicative, and chose to resolve conflicts positively. The implementation of anti-bullying and anti-racism character education proved effective in building attitudes of empathy, solidarity, and tolerance among elementary school students